Applications of a curvature correction turbulent model for computations of unsteady cavitating flows. Issue 2 (15th January 2015) - Zhao, Y; Wang, G Y; Huang, B; Hu, C L
Abstract: A Curvature Correction model (CCM) based on the original k-ϵ model is proposed to simulate unsteady cavitating flows. The objective of this study is to validate the CCM model and further investigate the unsteady vortex behaviors of cavitating flows around a Clark-Y hydrofoil. Compared with the original k-ϵ model, predicted results are improved in terms of the cavity detachment and hydrofoil fluctuations. Results show that streamline curvature correction of CCM model overcomes the over-predictions of turbulence kinetic energy and eddy viscosity in cavitating vertical region with the original k-ϵ model, which leads to better simulation abilities for the unsteady cavitating flow computations. Based on computations, it is proved that the vortex structure is significantly modified by the transient cavitation, especially with respect to the cavity shedding behaviors. Complex vortex interactions and corresponding cavity shedding process near hydrofoil trailing edge lead to various load frequencies.